2015
DOI: 10.1371/journal.pone.0118480
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Interaction of Wnt and RXR-α Pathways in Hepatocyte Development and Hepatocellular Carcinoma

Abstract: Genomic analysis of human hepatocellular carcinoma (HCC) is potentially confounded by the differentiation state of the hepatic cell-of-origin. Here we integrated genomic analysis of mouse HCC (with defined cell-of-origin) along with normal development. We found a major shift in expression of Wnt and RXR-α pathway genes (up and down, respectively) coincident with the transition from hepatoblasts to hepatocytes. A combined Wnt and RXR-α gene signature categorized HCCs into two subtypes (high Wnt, low RXR-α and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…RXR has a vital role in the transcription of tumor suppressor genes which induce differentiation and suppress cancer growth. 78 , 79 As NR4 subfamily nuclear receptors (e.g., Nur77, NURR1) are ubiquitous heterodimerization partners of RXR in forming heterodimers, 80 current study also revealed that when the cancer cells are incubated with HX600, a selective RXR agonist for Nur77-RXR and NURR1-RXR, the expression of CPTIA is induced through Nur77 or NURR1-mediated mechanism in the teratocarcinoma cells or heptoma carcinoma HepG2 cells 81 ( Figure 3 ).…”
Section: Regulation Of Cpti Expression In Cancer Cellsmentioning
confidence: 57%
“…RXR has a vital role in the transcription of tumor suppressor genes which induce differentiation and suppress cancer growth. 78 , 79 As NR4 subfamily nuclear receptors (e.g., Nur77, NURR1) are ubiquitous heterodimerization partners of RXR in forming heterodimers, 80 current study also revealed that when the cancer cells are incubated with HX600, a selective RXR agonist for Nur77-RXR and NURR1-RXR, the expression of CPTIA is induced through Nur77 or NURR1-mediated mechanism in the teratocarcinoma cells or heptoma carcinoma HepG2 cells 81 ( Figure 3 ).…”
Section: Regulation Of Cpti Expression In Cancer Cellsmentioning
confidence: 57%
“…3C; Supplemental Fig. S11), underscoring their importance in regulating liver-specific functions (Martinez-Jimenez et al 2010;DeLaForest et al 2011;Li et al 2015). Conversely, skin and cortex-specific genes exhibited a much lower enrichment for proximal DAP binding compared to liver-specific genes.…”
Section: Dap Binding Recapitulates Known Liver Expression Programsmentioning
confidence: 93%
“…We defined "liver-specific" genes as those with a mean RPKM, across all GTEx liver tissues, of at least two and at least five-fold higher than the mean RPKM in all other non-liver tissues. HNF4A and RXRA were the top TFs in terms of enrichment for binding near the TSSs of liver-specific genes ( Figure 3C, Supplemental Figure 9), underscoring their importance in regulating liverspecific functions (DeLaForest et al 2011;Martinez-Jimenez et al 2010;Li et al 2015).…”
mentioning
confidence: 91%